Aplicação da ferramenta 5s em uma obra de grande porte no município de Pau dos Ferros-RN - Vieira, Carlos Rangel Pereira (Universidade Federal Rural do Semi-Árido, 2019)
This study aimed to investigate the concepts of total quality using the 5S tool in a large work located in the city of Pau dos Ferros, RN. For this, data referring to a checklist applied at the study site were used. The research was classified as descriptive and quantitative, where it sought to generate quality indicator indices, using a scale from very poor to excellent. The main results indicate that the work presents itself as regular regarding its quality, being 51% positive regarding the 5S concept. The best service sector, rated as good, with 72% utilization was the armature cutting and bending environment. Regarding the senses analyzed, what refers to health was rated as excellent, meeting 100% of the specified in the checklist. In this way, it was possible to meet the proposed objectives and point out improvements in the site.
Keywords: Qualidade Total; Conceito 5S; Índices de Qualidade; Total Quality; Concept 5S; Quality Scores; CIENCIAS EXATAS E DA TERRA::CIENCIA E TECNOLOGIA